Concise Oxford English Dictionary - Edited by Stevenson, Angus and Waite, Maurice (Oxford Oxford University Press, 2011)
This centenary edition of the world-famous Concise Oxford English Dictionary presents the most accurate picture of English today
Keywords: English language